(untitled) (Baghdad Science Journal, 2017)
In this research four steps of the new derivatives of Naproxen drug have been made which are known as a high medicinal effectiveness; the first step involved converting Naproxen into the corresponding ester (A) by reaction Naproxen with methanol absolute in presence H2SO4. While the second step involved treatment methyl Naproxen ester (A) with hydrazine hydrate 80% in presence of ethanol .The third reaction requires synthesis of Schiff bases (C1-C10) by condensation. of Naproxen hydrazide (B) with many substituted aromatic aldehydes . Finally, the fourth step synthesized new tetrazole derivatives ( D1- D10) by the reaction of the prepared Schiff bases (in the third step) with Sodium azide in THF as a solvent .The prepared compounds were characterized by physical properties ,(FT-IR) ,UV, and somewhat of them by 1H-NMR, 13C-NMR spectroscopy.